2021
DOI: 10.33963/kp.a2021.0058
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and mid-term outcomes of nosocomial infection in ST-elevation myocardial infarction patients treated by primary angioplasty

Abstract: w w w . j o u r n a l s . v i a m e d i c a . p l / k a r d i o l o g i a _ p o l s k a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Szczepaniak et al [ 28 ] presented the inflammatory link between hypertension and periodontitis. Inflammatory reaction related to nosocomial infection was described as a possible risk factor for worse presentation and outcomes after acute coronary syndrome [ 29 ]. Moreover, Fan et al [ 30 ] identified a series of key genes closely related with inflammatory response and atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Szczepaniak et al [ 28 ] presented the inflammatory link between hypertension and periodontitis. Inflammatory reaction related to nosocomial infection was described as a possible risk factor for worse presentation and outcomes after acute coronary syndrome [ 29 ]. Moreover, Fan et al [ 30 ] identified a series of key genes closely related with inflammatory response and atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…As an important complication of STEMI, infection during hospitalization is associated with a worse clinical outcome [ 1 4 ], and several risk factors [ 24 , 25 ] and scores [ 4 , 26 , 27 ] are utilized for infection prediction and prevention. Unfortunately, these predictive tools are largely complex or unable to be interfered.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a simple and readily available pathophysiological biomarker of pulmonary infection is required to detect high risk patients as early as possible and ultimately improve their short-and long-term prognoses. Although several risk factors and scores are available to predict infection in patients with STEMI undergoing PCI, they are often complicated and are not easily applied 4,[7][8][9][10] .…”
Section: Endpoints and Definitionsmentioning
confidence: 99%